2018
DOI: 10.1155/2018/8246571
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Membrane Induced by Novel Biodegradable Nanofibers in the Masquelet Procedure for Treatment of Segmental Bone Defects

Abstract: The Masquelet induced-membrane technique for the treatment of segmental bone defects includes a two-stage surgical procedure, and polymethylmethacrylate (PMMA) plays a major role in the treatment. However, the PMMA spacer must be surgically removed. Here, we investigated the potential of poly(lactic-co-glycolic acid) (PLGA) nanofibers, a biodegradable material to replace the PMMA spacer, allowing the bioactive membrane to be induced and the spacer to degrade without the additional surgery on a rabbit femoral s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Finally, this systematic review focused on a single model to identify biomaterials that provided best results in IMT improvement. Other models are studied in this field notably the rabbit model that could bring additional data ( 29 ). Other strategies were not included in this work such as genetic studies ( 30 , 31 , 32 ), subcutaneous implantation of biomaterials ( 33 ), and other localization of bone defects ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this systematic review focused on a single model to identify biomaterials that provided best results in IMT improvement. Other models are studied in this field notably the rabbit model that could bring additional data ( 29 ). Other strategies were not included in this work such as genetic studies ( 30 , 31 , 32 ), subcutaneous implantation of biomaterials ( 33 ), and other localization of bone defects ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Yu et al found that the addition of fibrous PLGA to bone defects effectively improved the brittleness of CPC. A two-fold increase in toughness was observed in addition to a moderate improvement in compressive strength (Yu et al, 2018;Cai et al, 2023) (Figure 6). PLGA is effective in improving the handling properties of bone cement; it has also been widely used as a drug delivery system for molecules such as proteins, peptides, and genes due to its excellent carrier properties.…”
Section: Synthetic Polymersmentioning
confidence: 95%
“…Masquelet twostage procedure has the drawback of second procedure of removal of the PMMA spacer. To replace the PMMA spacer, Yi-Hsun Yu and colleagues has used biodegradable nanofibers in Masquelet procedure for treatment of segmental bone defects in animals [4]. We successfully used Septocoll E, an absorbable equine collagen fleece to work as pseudo membrane which has not been previously reported.…”
Section: Case Reportmentioning
confidence: 99%